Riparian Corridors: A New Conceptual Framework for Assessing Nitrogen Buffering Across Biomes - Pinay, Gilles; Bernal, Susana; Abbott, Benjamin W.; Lupon, Anna; Marti, Eugenia; Sabater, Francesc; Krause, Stefan (Frontiers in Environmental Science, 2018)
Anthropogenic activities have more than doubled the amount of reactive nitrogen circulating on Earth, creating excess nutrients across the terrestrial-aquatic gradient. These excess nutrients have caused worldwide eutrophication, fundamentally altering the functioning of freshwater and marine ecosystems. Riparian zones have been recognized to buffer diffuse nitrate pollution, reducing delivery to aquatic ecosystems, but nutrient removal is not their only function in river systems. In this paper, we propose a new conceptual framework to test the capacity of riparian corridors to retain, remove, and transfer nitrogen along the continuum from land to sea under different climatic conditions. Because longitudinal, lateral, and vertical connectivity in riparian corridors influences their functional role in landscapes, we highlight differences in these parameters across biomes. More specifically, we explore how the structure of riparian corridors shapes stream morphology (the river’s spine), their multiple functions at the interface between the stream and its catchment (the skin), and their biogeochemical capacity to retain and remove nitrogen (the kidneys). We use the nitrogen cycle as an example because nitrogen pollution is one of the most pressing global environmental issues, influencing directly and indirectly virtually all ecosystems on Earth. As an initial test of the applicability of our interbiome approach, we present synthesis results of gross ammonification and net nitrification from diverse ecosystems.